Serological Diagnostics of Lyme Borreliosis: Comparison of Universal and Borrelia Species-Specific Tests Based on Whole-Cell and Recombinant Antigens - Kodym, Petr; Kurzová, Zuzana; Berenová, Dagmar; Pícha, Dušan; Smíšková, Dita; Moravcová, Lenka; Malý, Marek (Journal of clinical microbiology, 2018)
The study compares diagnostic parameters of different commercial serological kits based on three different antigen types and correlates test results with the status of the patient's Borrelia infection. In total, 8 IgM and 8 IgG kits were tested, as follows: enzyme-linked immunosorbent assay (ELISA) (Euroimmun) based on whole-cell antigen, 3 species-specific enzyme immunoassays (EIAs) (TestLine), Liaison chemiluminescence (DiaSorin), ELISA-Viditest (Vidia), EIA, and Blot-Line (TestLine) using recombinant antigens. All tests were performed on a panel of 90 samples from patients with clinically characterized borreliosis (53 with neuroborreliosis, 32 with erythema migrans, and 5 with arthritis) plus 70 controls from blood donors and syphilis patients. ELISA based on whole-cell antigens has superior sensitivity and superior negative predictive value and serves as an excellent screening test, although its specificity and positive predictive values are low. Species-specific tests have volatile parameters. Their low sensitivity and low negative predictive value handicap them in routine diagnostics. Tests with recombinant antigens are characterized by high specificity and high positive predictive value and have a wide range of use in diagnostic practice. Diagnostic parameters of individual tests depend on the composition of the sample panel. Only a small proportion of contradictory samples giving both negative and positive results is responsible for discrepancies between test results. Correlation of test results with the patient's clinical state is limited, especially in the erythema migrans group with high proportions of negative and contradictory results. In contrast, IgG test results in the neuroborreliosis group, which are more concordant, show acceptable agreement with Borrelia status.
Keywords: protilátky bakteriální; lymeská nemoc; Borrelia; Immunoassay; Borrelia burgdorferi; antigeny bakteriální; reagenční diagnostické soupravy; lidé; Lyme disease; comparative studies; Sensitivity and Specificity; senzitivita a specificita; Antibodies, Bacterial; serology; immunoassays; imunoanalýza; sérologické testy; Lyme Disease; Antigens, Bacterial; Serologic Tests; Reagent Kits, Diagnostic; Humans